Genomics and Molecular Services in Developing Economies: a Suggested Road Map to Incorporate Technology in Parallel to the Emerging Landscape of Genetic Service Provision AI AI-Driven Arena - Khan, Sikandar Hayat; Khan, Muhammad Qaiser Alam; Hayat, Asma (Pakistan Armed Forces Medical Journal, 2025)
1. Science has never stayed static but has been evolving, revolutionizing, and opening out in 360 degrees. From the prehistoric invention of the wheel to the development of the “James Webb Telescope,” it was all hard work, allowing headway towards the envisioned redefinition of scientific discovery, which has led to the current day scientific boom. What we learn over time is that ‘change’ is the only constant in any human development and discovery. Recent landmark innovations of biotechnology and ambitious exploration of the human genome have allowed mining of the intricate ‘cellular life’ to enlighten our species with DNA and RNA world illuminating us with a tsunami of newer diagnostics and possibly therapeutics.1 Molecular sciences and genomics over recent decades to replace the conventional in clinical science with the potential to emerge as definitive medical tools for diagnostics. It can be an easy deduction to foresee that the genomics era has ushered in fast with more robustness to muscle much-needed depth now needed in clinical diagnostic care.2 The swarming growth of diagnostic markers has steadily entered the clinical corridors, necessitating a nationwide need for ‘standard of care in Molecular Pathology. 3